Efeito da suplementação sobre a qualidade seminal, libido e níveis séricos de insulina em touros cruzados (bos taurus taurus x bos taurus indicus) - Merchid, Nara Clara Lazaroni e (2017)
The objective of this study was to evaluate the effect of supplement on libido, sperm quality and serum insulin concentrations of mestizo and young bulls. Twelve healthy, pubescent, crossbred (3/4 Holstein x Gir) animals, averaging 19 months, were used. The animals were divided equally and randomly into the supplemented and control groups. Both groups are in the Brachiaria brizantha picket, with access to protein mineral salt and water ad libitum. The group supplemented with concentrate containing 20% crude protein and 70% of total digestible nutrients, with daily consumption of 1.0% of live weight of the animal from day 1 to day 70. As semen collections were carried out weekly without sector of the Federal Institute of Espírito Santo. (0-5), total sperm motility (%), vigor (0-5), sperm concentration (sptz / mL), sperm morphology, test (s), evaluated for color, odor, appearance, volume, (TTR) and hyposmotic test (HOST). On days 0, 35 and 70 it was performed for libido testing, animal weighing, circumference gauging and blood sample collection for measurement of insulin concentration measurement. The quantitative variables were evaluated in linear mixed models with measures repeated in time; the given scores for a libido variable to use for a questionable, good, very good and excellent rating. The frequencies of the distributions were arranged in contingency tables and as associations between the correction and the treatments as evaluated by Fisher's exact test or Freeman-Halton test. For as qualitative variables, used as Kruskall-Wallis test; a 5% significance level. There was no difference for motility, vigor with 180 min after collection, sperm concentration, total spermatozoa, viable spermatozoa, greater sperm morphology, hypostatic test and serum insulin concentrations. Significant difference was found for whirling, vigor at time 0 after collection and total and minor sperm morphology. As variables scrotal circumference, weight and mean daily gain are highly related to precocity and reproductive gain, and thus are positively influenced by treatment.